Ecotoxicological and Metabolism-Disrupting Actions of Bacillus thuringiensis israelensis and Deltamethrin Insecticides in Anuran Tadpoles - Empey, Madelaine (Université d'Ottawa / University of Ottawa, 2026)
Endocrine-disrupting chemicals are an increasing environmental concern due to their capacity to disrupt physiological processes, including growth, development, and metabolism. The insecticides VectoBac® 200G (a Bacillus thuringiensis israelensis (Bti) product) and deltamethrin (a pyrethroid) are widely used for mosquito control, but little research has examined their effects on amphibians. Here, we tested the hypothesis that VectoBac® 200G and deltamethrin adversely affect tadpole health and development via metabolic disruption. First, we assessed the toxicity of these insecticides on three North American species: the chorus frog (Pseudacris maculata), the leopard frog (Lithobates pipiens), and the wood frog (Lithobates sylvaticus). The 96 h median lethal concentration (LC50) values were estimated to be 513,000 ± 1.15, 78,860 ± 1.10, and 525,363.4 ± 1.13 international toxic units (ITU)/L for chorus, leopard, and wood frog tadpoles exposed to VectoBac® 200G. The LC50 values for deltamethrin were estimated to be 2.69 ± 1.06, 7.30 ± 1.05, and 1.15 ± 1.06 μg active ingredient (a.i.)/L for chorus, leopard, and wood frog tadpoles, respectively. VectoBac® 200G and deltamethrin had varying effects on total length, and investigations on metabolic endpoints were pursued in the wood frog tadpole. Metabolic studies on tadpoles are sparse, and the biggest challenge was measuring blood glucose, as wood frog tadpoles are too small to collect blood from. We therefore designed and validated a novel assay that enables measurement of whole-body glucose in individual tadpoles. Following 30-day exposures, VectoBac® 200G significantly increased glucose uptake, whereas exposure to deltamethrin did not. Chronic exposure from the early larval stage through metamorphosis delayed time to complete metamorphosis in VectoBac® 200G-exposed tadpoles, and tadpoles exposed to both insecticides displayed altered hepatic lipid accumulation. These results further suggested that metabolic endpoints were altered from exposure, especially to VectoBac® 200G. To investigate pancreatic effects, a novel custom antibody targeting the frog insulin B-chain was generated and validated. Both insecticides increased the proportion and nuclear radius of pancreatic beta-cells in exposed wood frogs. Only VectoBac® 200G increased total insulin-positive staining per pancreas; however, insulin staining per beta-cell decreased. Increased beta-cell proliferation combined with reduced insulin staining per cell suggests altered insulin dynamics in VectoBac® 200G-exposed frogs. Collectively, these results address data gaps for both Bti and deltamethrin insecticides and provide insight into potential mechanisms by which these products may disrupt amphibian metabolism.
Keywords: Ecotoxicology; Toxicology; Herpetology; Metabolism; Pre-diabetes; Insecticide